SIKAP MASYARAKAT BOGOR TERHADAP PROGRAM GREBEG PASAR - Ratih Siti Aminah; Yogaprasta Adinugraha; Budi Rhamdani (Universitas Pakuan, 2019)
ABSTRACTIONThis research aims to identify the customer's attitude toward a Grebeg Pasar of BRI, to describe the characteristics of individual traders Market Leuwiliang, to analyze the relationship between the characteristics of the individual account holders with attitude customer to a Grebeg Pasar of BRI. This research uses the free variable that is characteristic of the individual customer. While the free variable is a client's attitude to a Grebeg Pasar in the market at Leuwiliang BRI. The indicators used to measure individual customer characteristics variables are age, gender, level of education, UMKM business sector and the status of marriage. The indicators used to measure customer attitude variable to a Grebeg Pasar that is the shape of a Grebeg Pasar program, a form of lending products, promotional forms a Grebeg Pasar. Research done at Market Leuwiliang in may 2016. Samples taken is all the population that is as much as 90 businessmen. Sampling techniques are used is total sampling. The source of the data used include primary data such as questionnaires, interviews and observations to the respondents research and secondary data such as previous research results that are relevant, the books, the source of scientific data from Market Leuwiliang, Bogor. Technique of data analysis using statistical analysis descriptive and non-parametric statistical analysis. Test correlation using the formula Spearman Rank test with the validity of using the formula product moment Pearson. Analysis of variable X1 regarding characteristics of individual traders (customers) and the variable Y1 is attitude towards client program a Grebeg Pasar of BRI. The results of the relationship between the characteristics of individual employees and employee perception toward the leadership style elicited less significant relationships. Keywords: Attitude, Customer Programs, Grebeg Pasar